Quadriceps tendon vs. patellar tendon autograft for ACL reconstruction using a hardware-free press-fit fixation technique: comparable stability, function and return-to-sport level but less donor site morbidity in athletes after 10 years - Barié, Alexander; Sprinckstub, Thomas; Huber, Jürgen; Jaber, Ayham (Archives of orthopaedic and trauma surgery, 2020)
The use of quadriceps tendon-patellar bone (QTB) autograft for anterior cruciate ligament (ACL) reconstruction is gaining momentum. Yet, long-term results that compare this procedure with established methods are lacking. The aim of this study was to report and compare long-term results of ACL reconstruction using QTB autografts versus bone-patellar tendon-bone (BPTB) autografts, both anchored using a hardware-free press-fit fixation technique.
Gesehen am 27.10.2021